Polyphenols and Antioxidants in Masyaura - Dahal, Nawa Raj; Qi, Li (Journal of Food Science and Technology Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Masyaura, a legume based traditional fermented food product of Nepal, prepared from blackgram dhal and colocosia tuber by different fermentation methods were evaluated for polyphenol and antioxidant characteristics. Total polyphenol content of Masyaura ranged from 235 to 351 mg/100g on dry matter. Blackgram dhal and colocosia tuber showed polyphenol content higher (P=0.05) as compared to Masyaura showing the value of 838 and 826 mg/100g respectively. Tannin content in Masyaura was found in the range of 101 to 131 mg/100g. Total reactive antioxidant potential (TRAP) value in Masyaura was found in the range of 7.6 to 10.6 mM as ascorbate on dry matter; while blackgram dhal and colocosia tuber showed TRAP value of 9.9 and 23.4 respectively. Antioxidant property was found to be higher (P=0.05) in stored Masyaura as compared to the fresh one. Key words: Masyaura; Polyphenol content; TRAP value; Fermented food; Nepal Journal of Food Science and Technology Nepal Vol. 4, September, 2008, Page: 43-46